A COMMOGNITIVE STANDPOINT: THE PROCESS OF PROBLEM-SOLVING IN POLYHEDRON - Azizah, Fita Nuril; Wulan, Eka Resti; Rahayu, Dwi Shinta (Jurnal Pendidikan Matematika dan IPA, 2023)
Abstract This study aims to describe students"™ commognitive in the process of solving the problem in polyhedron, based on the four stages of Polya. This study uses an approach with a descriptive type of research. The instruments used in this study were in the form of problem solving test questions and interview guidelines. The subjects of this study were students of class VIII in one of the schools in the Nganjuk district. The result of this research is that at each stage of problem solving students use cognitive components. Narrative components that affect students' success in solving problems, as seen in the results of subject answers. This shows that narrative has an important role in the problem solving process. The narrative component is related to understanding mathematical concepts, so it is hoped that in learning students can understand concepts. The results of this study indicate that students are still more focused the final solution and attention to an important component in the problem solving process, in this case is the commognitive component.